Laparoscopic training in colorectal surgery: can we do it safely? - Lobato,Luiz Felipe de Campos (2013)
OBJECTIVE: Laparoscopic approach should be offered for most patients requiring colectomy, as it is a safe procedure, associated with shorter hospitalization, better cosmetic results, and does not affect negatively the oncological outcomes of patients with colon cancer. However, there is no consistent data on the safety of laparoscopic surgery training during residency. Therefore, the aim of this study was to assess whether or not the resident participation in laparoscopic colectomy affected the postoperative outcomes. METHODS: The database of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) was searched for patients undergoing laparoscopic colectomies between 2005 and 2007. We excluded patients with no data regarding whether or not there was a resident participation in the operation. The study population was divided into 2 groups (resident and nonresident), according to residents participation in the surgical procedure. Perioperative variables and postoperative complications were compared between groups. A multivariate analysis was performed to evaluate the association between postoperative complications and resident participation in the operation. RESULTS: The search yielded 5,912 patients with a median age of 63 years. Of these, 3,112 (53%) were female and 3.887 (66%) had a resident involved in their operation. The resident group had a significantly longer mean operative time (163 ± 64 min vs 138 ± 58 min, p < 0.0001). Other variables did not differ significantly between groups. Moreover, multivariate analysis showed no association between resident participation and the occurrence of postoperative complications. CONCLUSION: Laparoscopic training during residency may be safely performed without threatening the patient's integrity.